PENGARUH PEMBELAJARAN KOOPERATIF KOMBINASI MEDIA QUIZIZZ TERHADAP HASIL BELAJAR SISWA - Filliana Asri Lestari; Siti Nur Faridah; Syarifatul Maf’ulah; Faridatul Masruroh (TRANSFORMASI, 2023)
This research is motivated by the lack of student motivation in learning mathematics, so there is a need for learning innovation. One of them is by utilizing learning media, namely Quizizz media. The purpose of this study was to determine the effect of cooperative learning using the Quizizz media combination on student learning outcomes, with quantitative research type. The research sample was students of class VI-A MI Sulaimaniyah Kauman Mojoagung as many as 34 students from the entire population of class VI students as many as 122 students. The research instrument is in the form of test questions (pretest and posttest). Data analysis used the paired sample mean test with the help of the SPSS program. The research hypothesis is that there is an effect of cooperative learning using the Quizizz media combination on the learning outcomes of class VI students at MI Sulaimaniyah. Based on the output of SPSS version 20, it can be seen that the results of the study are in the form of a Sig.(2-tailed) value of H0 is rejected and H1 is accepted. So, there are differences in student learning outcomes with and without using the Quizizz media combination cooperative learning at MI Sulaimaniyah Kauman Mojoagung in mathematics. As a results, it can be said that there is an influence on student learning outcomes by using cooperative learning, a combination of Quizizz media, and the learning is very effectively used in the elarning process for class VI students at MI Sulaimaniyah Kauman Mojoagung.